A phase I trial of afatinib and bevacizumab in chemo-naïve patients with advanced non-small-cell lung cancer harboring EGFR mutations: Okayama Lung Cancer Study Group Trial 1404. (January 2018) - Ninomiya, Takashi; Nogami, Naoyuki; Kozuki, Toshiyuki; Harada, Daijiro; Kubo, Toshio; Ohashi, Kadoaki; Kuyama, Shoichi; Kudo, Kenichiro; Bessho, Akihiro; Fukamatsu, Nobuaki; Fujimoto, Nobukazu; Aoe, Keisuke; et al.
Highlights: A phase I study of afatinib and bevacizumab for EGFR mutant patients was performed. Afatinib 30 mg/day plus bevacizumab 15 mg/kg every 3 weeks was tolerable. Afatinib plus bevacizumab showed evidence of favorable disease conrtol. Abstract: Objective: In advanced epidermal growth factor receptor (EGFR)-mutant non-small-cell lung cancer (NSCLC), treatment with afatinib, a second-generation EGFR-tyrosine kinase inhibitor (TKI), confers a significant survival benefit over platinum-based chemotherapy. The first-generation EGFR-TKIs gefitinib and erlotinib in combination with bevacizumab have improved progression-free survival. We hypothesized that the combination of afatinib with bevacizumab would further improve efficacy, and conducted a phase I trial to test this hypothesis. Materials and methods: Untreated patients with advanced EGFR-mutant NSCLC were enrolled. The primary endpoint was safety. Two doses of afatinib, 40 mg/day (level 0) and 30 mg/day (level −1), were evaluated in combination with 15 mg/kg bevacizumab every 3 weeks. Optimal dosing was determined by dose-limiting toxicity (DLT), with the concentration at which ≤4 of 12 patients experienced toxicity considered the recommended dose. Results: Nineteen patients were enrolled (level 0:5, level −1:14). Three of the five patients at level 0 experienced a DLT, which indicated that this dose was unfeasible. Three patients at level −1 developed a DLT of grade 3 non-hematological toxicity, which was soon resolved. Grade 3 or worse adverse events were experienced by all five patients at dose level 0 (diarrhea in 2, skin rash in 1, hypoxia in 1, and paronychia in 1), and by three patients at level −1 (diarrhea in 2 and anorexia in 1). Among 16 evaluable patients, 1 had a complete response, 12 had partial responses, and 0 had progressive disease. Conclusion: Afatinib plus bevacizumab (level −1) was well tolerated and showed evidence of favorable disease control. This combination therapy may represent a potent therapeutic option for patients with EGFR-mutant NSCLC.